1991
DOI: 10.1159/000125940
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cold Exposure on the Hypothalamic Release of Thyrotropin-Releasing Hormone and Catecholamines

Abstract: The effects of cold exposure on the release of thyrotropin-releasing hormone (TRH) and catecholamines as estimated by push-pull perfusion of the mediobasal hypothalamus were studied. Before cold exposure, the male rats had been kept at room temperature or at 30 °C for 3 weeks. Transfer to 4 °C increased plasma levels of thyroid-stimulating hormone (TSH), but this cold-induced TSH response was more pronounced in animals which had been acclimatized to 30 ° C. Exposure to 4 ° C also increased plasma thyroid hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 26 publications
2
27
0
2
Order By: Relevance
“…In rats, cold temperatures increase TRH mRNA levels in the hypothalamic paraventricular nucleus (46), augment TRH release from the median eminence (47), stimulate TSH secretion from pituitary, and potentiate T 4 and T 3 contents in blood (48). In our studies, basal levels of serum TSH and T 4 are similar among WT, heterozygous, and Cpe fat/fat mice.…”
Section: Pro-trh Processing and Thermal Responses In Cpesupporting
confidence: 53%
“…In rats, cold temperatures increase TRH mRNA levels in the hypothalamic paraventricular nucleus (46), augment TRH release from the median eminence (47), stimulate TSH secretion from pituitary, and potentiate T 4 and T 3 contents in blood (48). In our studies, basal levels of serum TSH and T 4 are similar among WT, heterozygous, and Cpe fat/fat mice.…”
Section: Pro-trh Processing and Thermal Responses In Cpesupporting
confidence: 53%
“…In our previous experiments, acute cold exposure resulted in a marked elevation in plasma norepinephire levels together with a modest elevation of plasma adrenocorticotropic hormone (ACTH) and corticosterone levels [20]. Although previous investigators have reported changes in brain catecholamine levels in response to cold stress [21, 22, 23], we have identified that cold exposure induces only a small increase in the paraventricular (PVN) norepinephrine level compared to other types of stressful stimuli, like immobilization or formalin-induced pain [19]. Therefore, tyrosine hydroxylase (TH) immunostaining was combined with Fos immunostaining to examine the possible role of catecholaminergic neurons in the organization of cold stress responses.…”
Section: Introductionmentioning
confidence: 99%
“…In response to a cold stress, catecholaminergic afferents from the brain stem onto the PVN rapidly contribute to increase Crh and Trh mRNA levels in the PVN, concomitant with the release of TRH, TSH, and corticosterone (Zoeller et al 1990, Rondeel et al 1991, Uribe et al 1993. The changes in Trh mRNA are transient, with increases at 1 h and normalizing by 2 h, even when animals are kept in the cold for long periods; Trh mRNA levels rise again at 6 h but only if animals are exposed during the light period (Uribe et al 1993, Zoeller et al 1995.…”
Section: Hpt Responses To Acute Stimulimentioning
confidence: 99%
“…The most commonly used sensor of activation of TRH neurons has been the measurement of Trh mRNA levels. Rapid (!2 h) changes in TRH tissue concentration, mostly concentrated at nerve endings have been used as an indirect marker of TRH release because at later times TRH content represents the resultant of synthesis and release but not of degradation because the intracellular peptidases do not modulate TRH levels within secretory granules (Rondeel et al 1991, van Haasteren et al 1995, Aguilar-Valles et al 2007.…”
Section: Introductionmentioning
confidence: 99%